Peran Pemimpin dalam Perubahan Organisasi Pendidikan - Muhammad Eko Purwanto; Ismail Hasim (Jurnal Indragiri Penelitian Multidisiplin, 2023)
Organizational change requires a leadership role and group decision involvement. Leadership is a leader's process of influencing followers to interpret circumstances, selecting organizational goals, organizing work and motivating followers, maintaining cooperation and teamwork, and organizing support and cooperation with outsiders of the organization. The purpose of this research, namely: 1). To understand the leader in carrying out project work; 2). To understand leaders organize change engines; 3). To understand leaders mobilize Resources in Organizations; 4). To understand leaders motivating change in educational organizations. Methods and analysis in this library research were carried out in a descriptive-qualitative manner, while data processing was carried out by systematizing materials or books. Systematization means making a classification of existing materials. The results of this study, among others, show that changes in the organization include the stages of preparation/unfreezing, change, and re-freezing. A leader in a change must set change objectives, take and determine decisions about what changes should be made, determine the timeframe needed to make and occur organizational changes and bear all risks to the organization that may arise as a result of decisions about changes.